Pengaruh Fraksi Volume Serat Pelepah Gebang (Corypha Utan Lamarck) Terhadap Sifat Mekanik Pada Komposit Bermatrik Epoksi - Johanis Abanat, Jufra Daud; Purnowidodo, Anindito; Irawan, Yudy Surya (Jurnal Rekayasa Mesin, 2012)
Buri Palm trees (Corypha Utan Lamarck) is one of the many types of flora in Indonesia that has not been used optimally. At the leaf midrib of buri palm has fibers that have not been developed from the engineering side. There for in this study used buri palm leaf midrib fiber as an alternative reinforcement material for manufacturing of epoxy composites that can be useful for manufacturing the body of boat, the interior of boat and also for helmets. Thus, this study aims to determine the tensile strength and impact strength of the material in accordance with the desired application. Before being used the fiber from the buri palm leaf midrib should be tested of the tensile strength and the data obtained at 182,24 MPa. Then also tested Alkali treated fiber NaOH 5% and a maximum tensile strength obtained is 212,29 MPa on the sample by treatment for 2 hours. Base on these preliminary data then manufacturing of composite samples using fibers of alkaline NaOH 5% treatment for 2 hours. Variations of fiber volume fraction are from 0%, 10%, 20%, 30%, 40%, 50%, 60% and 70%. The tensile testing sample based on the ASTM D638-3 standard and impact test samples according to ISO 179-1 standard. From the test results is known that the tensile strength of composites increases with increasing fiber volume fraction up to 70% of fiber that is equal to 51,993 MPa. Impact strength also increased up to 70% fiber volume fraction and the maximum impact strength occured is 6,953 J.Keywords: composite, buri fiber, epoxy, volume fraction